The effect of new proteasome inhibitors, belactosin A and C, on protein metabolism in isolated rat skeletal muscle - Muthny, T; Kovarik, M; Sispera, L; de Meijere, A; Larionov, O V; Tilser, I; Holecek, M (Journal of physiology and biochemistry, 2009)
The proteasome inhibitors are used as research tools to study of the ATP-dependent ubiquitin-proteasome system. Some of them are at present undergoing clinical trials to be used as therapeutic agents for cancer or inflammation. These diseases are often accompanied by muscle wasting. We herein demonstrate findings about new proteasome inhibitors, belactosin A and C, and their direct effect on protein metabolism in rat skeletal muscle. M. soleus (SOL) and m. extensor digitorum longus (EDL) were dissected from both legs of male rats (40-60 g) and incubated in a buffer containing belactosin A or C (30 microM) or no inhibitor. The release of amino acids into the medium was estimated using high performance liquid chromatography to calculate total and myofibrillar proteolysis. Chymotrypsin-like activity (CTLA) of proteasome and cathepsin B, L activity were determined by fluorometric assay. Protein synthesis and leucine oxidation were detected using specific activity of L-[1-14C] leucine added to medium. Inhibited and control muscles from the same rat were compared using paired t-test. The results indicate that after incubation with both belactosin A and C total proteolysis and CTLA of proteasome decreased while cathepsin B, L activity did not change in both SOL and EDL. Leucine oxidation was significantly enhanced in SOL, protein synthesis decreased in EDL. Myofibrillar proteolysis was reduced in both muscles in the presence of belactosin A only. In summary, belactosin A and C affected basic parameters of protein metabolism in rat skeletal muscle. The response was both muscle- and belactosin-type-dependent.
Keywords: mezibuněčné signální peptidy a proteiny; Rats; Male; chymotrypsin; svalové proteiny; Intercellular Signaling Peptides and Proteins; Proteasome Inhibitors; Rats, Wistar; mužské pohlaví; Muscle, Skeletal; kathepsin B; Cathepsin B; Chymotrypsin; krysa rodu Rattus; Peptides; zvířata; inhibitory proteasomu; kosterní svaly; Muscle Proteins; peptidy; potkani Wistar; aminokyseliny; Amino Acids; Animals